Caseous Necrosis of Mitral Annulus - Sinan Balci; Selcuk Akkaya; Selin Ardali; Tuncay Hazirolan (Case Reports in Radiology)
Masses or mass-like lesions located in proximity to mitral valve encompass a wide range of differential diagnoses including neoplasias, abscesses, thrombi, and rarely caseous calcification of mitral annulus. Due to asymptomatic presentation, its diagnosis is usually incidental. Echocardiography is the first choice of imaging in evaluation. Cardiac computed tomography (CT) is helpful in establishing diagnosis by showing dense calcifications while cardiac magnetic resonance imaging (MRI) is used primarily as a problem solving tool. Imaging in evaluation of mitral annulus caseous calcification is essential in order to prevent unnecessary operations.